Analisis financiero de las cuentas por cobrar de Tecnicentro “El Trueno” ciudad de Babahoyo - Santos Yépez, Gabriela Natali (2019)
The objective of this study is to compare accounts receivable in an accounting manner through a financial analysis generated by the company, a factor that is used to consider obtaining a loan, which allows us to grant it with greater security. The methodology is descriptive type since it is the one that allows to analyze facts that incur within the entity. The company presents a problem at the time of recovering the credits that are granted to customers since there was an increase in the last year of 45 days. Tecnicentro presents a serious problem due to its sales that are made on credit despite not having credit and collection policies that allow it to take control of this item